2021
DOI: 10.1021/acs.cgd.1c00507
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Faceted Mesocrystals: Advances in Optimization of Growth Conditions

Abstract: One aspect of the research on mesocrystals nowadays focuses on applications, whereby such applications demand mesocrystals with a tunable size. To achieve this task, more effort needs to be undertaken to understand how mesocrystals form, which parameters influence mesocrystal formation, and which kind of structure results from the nanoparticle assembly. Within this communication, we demonstrate for faceted mesocrystals assembled from iron oxide nanocubes stabilized by oleic acid that the proper choice of cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 41 publications
(66 reference statements)
3
20
0
1
Order By: Relevance
“…55 We also performed the optimization of crystallization conditions in the gas phase diffusion technique and showed that the appropriate choices of substrate, dispersion, destabilizing agents, concentration of additive (acting as stabilizer and depletion agent), and nanocrystals (the size and shape distribution could be narrowed by multiple recrystallization 56 ) allow faceted mesocrystals to grow with sizes from a few micrometers up to the millimeter range. 57 Furthermore, we confirmed that the external magnetic field could significantly affect the assembly process and change the morphology of aggregates and orientational order of nanoparticles. 52 This paper aims to provide a systematic study of morphogenetic aspects of mesocrystals and represents an important step forward compared to our previous study.…”
Section: ■ Introductionsupporting
confidence: 53%
“…55 We also performed the optimization of crystallization conditions in the gas phase diffusion technique and showed that the appropriate choices of substrate, dispersion, destabilizing agents, concentration of additive (acting as stabilizer and depletion agent), and nanocrystals (the size and shape distribution could be narrowed by multiple recrystallization 56 ) allow faceted mesocrystals to grow with sizes from a few micrometers up to the millimeter range. 57 Furthermore, we confirmed that the external magnetic field could significantly affect the assembly process and change the morphology of aggregates and orientational order of nanoparticles. 52 This paper aims to provide a systematic study of morphogenetic aspects of mesocrystals and represents an important step forward compared to our previous study.…”
Section: ■ Introductionsupporting
confidence: 53%
“…We assume that a reduced particle concentration prevents the IONCs from reaching a critical particle concentration (CPC) during the gas-phase diffusion process within the set crystallization period of 14 days, which would otherwise trigger IONC cluster formation and ultimately result in a monophase mesocrystal formation. [19,45] Nevertheless, the self-assembly of a less concentrated binary particle mixture resulted in the formation of 3-5 mm sized, uniform superlattices, which are much smaller in size than the compared IONP host lattice binary mesocrystals. As previous research has shown that the obtained mesocrystal size is directly connected to the concentration of the parent particle dispersion, [45] our results confirm that such assumption is also valid for the formation of binary mesocrystals.…”
Section: Resultsmentioning
confidence: 99%
“…[19,45] Nevertheless, the self-assembly of a less concentrated binary particle mixture resulted in the formation of 3-5 mm sized, uniform superlattices, which are much smaller in size than the compared IONP host lattice binary mesocrystals. As previous research has shown that the obtained mesocrystal size is directly connected to the concentration of the parent particle dispersion, [45] our results confirm that such assumption is also valid for the formation of binary mesocrystals. [46] Besides the smaller size of the crystals, FE-SEM images shown in Figure 6 a,c display an increase in IONC incorporation when compared to the respective PtNC incorporation of an IONC host lattice binary mesocrystal.…”
Section: Resultsmentioning
confidence: 99%
“…We assume that areduced particle concentration prevents the IONCs from reaching acritical particle concentration (CPC) during the gas-phase diffusion process within the set crystallization period of 14 days,w hich would otherwise trigger IONC cluster formation and ultimately result in am onophase mesocrystal formation. [19,45] Nevertheless,t he self-assembly of al ess concentrated binary particle mixture resulted in the formation of 3-5 mm sized, uniform superlattices,w hich are much smaller in size than the compared IONP host lattice binary mesocrystals.As previous research has shown that the obtained mesocrystal size is directly connected to the concentration of the parent particle dispersion, [45] our results confirm that such assumption is also valid for the formation of binary mesocrystals. [46] Besides the smaller size of the crystals,F E-SEM images shown in Figure 6a,c display an increase in IONC incorporation when compared to the respective PtNC incorporation of an IONC host lattice binary mesocrystal.…”
Section: Methodsmentioning
confidence: 99%